1999
DOI: 10.1124/mol.56.5.982
|View full text |Cite
|
Sign up to set email alerts
|

Lead Inhibition of DNA-Binding Mechanism of Cys2His2Zinc Finger Proteins

Abstract: The association of lead with chromatin in cells suggests that deleterious metal effects may in part be mediated through alterations in gene function. To elucidate if and how lead may alter DNA binding of cysteine-rich zinc finger proteins, lead ions were analyzed for their ability to alter the DNA binding mechanism of the Cys(2)His(2) zinc finger protein transcription factor IIIA (TFIIIA). As assayed by DNase I protection, the interaction of TFIIIA with the 50-bp internal control region of the 5S ribosomal gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 29 publications
1
49
0
1
Order By: Relevance
“…As these author point out, one potential mechanism of Pb 2+ -induced decrease on progenitor cell proliferation may be due to its inhibitory effects on DNA binding of zinc finger transcription factors such as Sp1 and TFIIIA (Zawia et al, 1998;Hanas et al, 1999). An alternative mechanism by which chronic Pb 2+ exposure alters granule cell neurogenesis may be related to alterations in NMDAR function (Nacher and McEwen, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…As these author point out, one potential mechanism of Pb 2+ -induced decrease on progenitor cell proliferation may be due to its inhibitory effects on DNA binding of zinc finger transcription factors such as Sp1 and TFIIIA (Zawia et al, 1998;Hanas et al, 1999). An alternative mechanism by which chronic Pb 2+ exposure alters granule cell neurogenesis may be related to alterations in NMDAR function (Nacher and McEwen, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, incubation of cell extracts with Cd 2+ inhibits MTF-1 binding to its cognate metal response elements according to an EMSA [19]. Hanas et al have also demonstrated that preincubation of Zn-TFIIIA with Pb 2+ prevents specific protein binding to the ICR [27,29]. Nevertheless, Cd 2+ -substituted Sp1 has been shown to be active in DNA binding [28].…”
Section: Discussionmentioning
confidence: 99%
“…As for Pb 2+ , in spite of its pervasiveness as an environmental contaminant, data about its interaction with zinc finger proteins has been lacking until recently. Hanas et al have reported that Pb 2+ inhibits the interaction of TFIIIA with the ICR [27,29]. Godwin and her coworkers have shown that Pb 2+ forms complexes with other zinc finger peptides which vary in the number of cysteine and histidine ligands [30].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Azooz et al (2011) reported that a high dose combination of Zn and Pb produced a synergystic effect on the inhibition of plant growth parameters. Hanas et al (1999) also reported that Pb inhibited the binding of Zn to proteins. Protein binding was reported to be higher for Pb than for Ca and Zn (Hasiang and Diaz, 2011;Godwin, 2001).…”
Section: Discussionmentioning
confidence: 96%
“…Park et al (2001) reported that MT did not provide protection against Pb and Fe. The differences in results between the studies may be the result of the different doses used and variations between animal species utilised, which covered a wide scale, including rats and cows (Hanas et al,1999;Verster 2011).…”
Section: Discussionmentioning
confidence: 99%